"Hope for good luck" during the COVID-19 pandemic - Kiiko, Yurii (Current Problems of Psychiatry, 2024)
Introduction: The situation with COVID-19 is unexpected and unpredictable, and the consequences are tragic. The number of sick and dead has increased globally, including in Ukraine, and it is reasonable to assume that this will have a certain effect on the mental state of people, including their level of anxiety. Therefore, this study focuses on measuring the level of state anxiety and determining its relationship with the perception of various aspects of COVID-19 by the population of Ukraine. Material and methods: The survey was conducted by telephonic interview. Respondents were recruited randomly in the period from 17.04 to 22.05.2020. The sample consists of 412 people from all over Ukraine. State anxiety, which is dynamic and reflects the level of anxiety on the State Anxiety Scale from The State-Trait Anxiety Inventory (STAI) at a particular time, was studied. Results: Differences have been traced in responses of male and female respondents, where this indicator was higher among females. People tend to have a different subjective attitude towards the likelihood of finding themselves in the same situation, which for objective reasons is relatively equal for everyone who is in the same pandemic environment; they tend to believe they are more likely to protect themselves from the disease than those around them. Individuals tend to overestimate both their ability to achieve a certain success in the situation and the favorable circumstances ("hope for good luck"). There is a certain correlation between this assessment and the level of state anxiety (correlation = 0.2328 (p <0.01)), i.e. the higher the anxiety, the higher a person estimates the probability of contracting the disease themselves or of others falling ill. There are two extremes in the Ukrainian society: the part of the population that reasonably estimates their place in the world (if it is a global problem, and I am a part of the world then this is my problem) constitutes 42% of respondents who participated in the study; the part of the population that tends to separate themselves from the society as a whole (state anxiety in this group is lower) – this is a problem of the world but not mine (and am I a part of the world?) – constitutes 41%. Conclusions: State anxiety is almost independent of characteristics, such as age, gender, or place of residence, but this anxiety differs among people with different views of themselves and their place in society, which necessitates some in-depth research of other personal factors in parallel with state anxiety that could further clarify the situation.